Undernutrition and associated factors in orphan children aged 6–59 months in Gambella Southwest, Ethiopia: A community-based cross-sectional study - Feleke, Solomon (BMJ Open, 2021)
OBJECTIVE: The study aimed to assess the prevalence of stunting, wasting, underweight and associated factors in orphaned children under 5 years old. DESIGN: A cross-sectional study. SETTING: Gambella City, Ethiopia. PARTICIPANTS: A sample of 419 under 5 orphaned children included in the study. Eligible households with orphans had selected using a systematic random sampling method. The lottery method was used when more than one eligible study participants live in the household. An OR with 95% CI was performed to measure the strength of association between each dependent variable and independent variables. Variables with p<0.05 were declared statistically significant. PRIMARY OUTCOME: The main outcome of this study was the prevalence of undernutrition among orphaned under 5 and its associated factors. RESULTS: Prevalence of stunting, wasting and underweight in orphan children under 5 were 12.2%, 37.8% and 21.7%, respectively. The prevalnce of wasting peaks among age group of 36–47 months (42.5%), whereas underweight peaks in 48–59 months (27.7%). Food insecurity, wealth index, family size, vitamin A supplementation, diarrhoea, fever 2 weeks before the survey, children under 5 and parents’ death were associated with undernutrition. CONCLUSION: The prevalence of stunting, wasting and underweight among orphan children under 5 was significantly high. Multisectoral collaborative efforts towards access to health services, improving income-generating activities, micronutrient supplementation and social support and protection targeting orphan and vulnerable populations have to be built up.